Governing Cultures: Anthropological Perspectives on Political Labor, Power, and Government - Coulter, Kendra; Schumann, William R. (Palgrave Macmillan, 2012)
Governments are formal political institutions, places of work for thousands of women and men, and powerful social, cultural, and economic sites that shape the lives of all people. This collection demonstrates how anthropologists enrich our understandings of government by exploring the labor of those who govern, and how the dynamics of culture are at the heart of government actions that justify, modify, and reproduce political action. By assembling original, ethnographically-grounded research in legislatures, executives, and bureaucracies, this volume illuminates and unpacks the structures, practices, and values of government actors in local, regional, and national contexts. It will be of interest to scholars and students in anthropology, as well as sociology, political science, policy studies, and labor studies. –Publisher's description
OCLC: 781432429
Keywords: Anthropologie politique; Government policy; Legislative power; Political anthropology; Pouvoir législatif